Integrasi agama dan sains dalam pendidikan keimanan: Perspektif Rasail al-Nur karya Said Nursi - Fitrowan, Moh. Salis (Tawazun: Jurnal Pendidikan Islam, 2023)
Western-oriented education is sometimes far from the goal of tafakur or introducing the Creator, Allah Swt, to students. In contrast, the concept of education initiated by Said Nursi in his book Rasail al-Nur reflects the integral value between religion and science so as to foster faith. Using descriptive qualitative method, this research tries to find the purpose of integrative faith education between religion and science. The results of the study found several objectives of faith education contained in the integration between religion and science in Said Nursi's thought, namely: Makrifatullah or knowing Allah, strengthening faith, understanding the Quran as a guide to life, understanding the nature of natural creation, and understanding the supernatural realm. Abstrak Pendidikan yang berkiblat kepada barat terkadang jauh dari tujuan untuk tafakur atau memperkenalkan Pencipta, Allah Swt., kepada peserta didik. Berbeda dengan konsep pendidikan yang digagas Said Nursi pada kitabnya Rasail al-Nur mencerminkan nilai integral antara agama dan sains sehingga menumbuhkan keimanan. Dengan metode kualitatif deskriptif, penelitian ini mencoba menemukan tujuan pendidikan keimanan yang integratif antara agama dan sains. Hasil penelitian menemukan beberapa tujuan pendidikan keimanan yang termuat di dalamnya integrasi antara agama dan sains dalam pemikiran Said Nursi yaitu: Makrifatullah atau mengenal Allah, memperkuat keimanan, memahami Alquran sebagai pedoman hidup, memahami hakikat penciptaan alam, dan memahami perihal alam gaib.